Comparative study on the selective laser sintering of polypropylene homopolymer and copolymer : processability, crystallization kinetics, crystal phases and mechanical properties - Tan, Lisa Jiaying (2021)
Isotactic polypropylene homopolymer (iPP) and copolymer (CoPP) were comparatively investigated for selective laser sintering (SLS). The processability of the polymer powders was evaluated in terms of powder morphology, powder flowability, melting behavior, and crystallization kinetics. An isothermal differential scanning calorimetry (DSC) testing protocol was employed as an effective and efficient method to facilitate the determination of suitable powder bed temperature. The results showed that the sintering window of iPP (26.3 ℃) was similar to that of polyamide 12 (PA12) (25.8 ℃), while CoPP had a narrower sintering window (2.2 ℃), making it much less tolerant to temperature deviations that occur during printing, and thus more prone to warping. The crystallization activation energy values of iPP and CoPP were ∼60 % that of PA12, suggesting that both of the PP materials were less sensitive to temperature fluctuations close to their crystallization temperatures. At optimal processing parameters, the ultimate tensile strength and elongation at break values of the printed iPP and CoPP specimens were found to be 14.9 MPa and 1 %, and 19.5 MPa and 207 %, respectively. Importantly, it was established that for PP with high regio- and stereo-irregularities, such as CoPP, SLS serves as a viable alternative manufacturing technique for producing PP parts comprising γ-phase crystals that are difficult to manufacture by conventional moulding processes.